Effects of garcinia mangostana on adipocyte differentiation and glucose uptake regulation in 3T3-L1 cells - Bakhtiar, M. Taher; Tengku Zakaria, Tengku Muhammad Faris Syafiq (2014)
Background: Garcinia mangostana Linn. (GME) or mangosteen also known as ‘queen of fruits’ is a tropical plant and can be found in Southeast Asia region. The pericarps are utilized as traditional medicines to treat various ailments like abdominal pain, diarrhea, dysentery, infected wounds, suppuration and chronic ulcer attributed to secondary metabolites like xanthones (crenelated and oxygenated), tannins, anthocyanins, triterpenes, phenolics, polysaccharides, vitamins B1, B2 and C. Aim: The present study was delineated to elucidate the effects of ethanolic extract (GME) on preadipocyte differentiation of 3T3-L1 cell and the possible glucose uptake mechanism signifying the potential to lower plasma glucose concentration in vivo. Methods: Adipocyte cells were cultured in DMEM containing 1% penicillin–streptomycin (PS) and 10% fetal bovine serum (FBS) at 37oC in a humidified 5% CO2 atmosphere. Differentiation was initiated after 2-day post-confluent in MDI inducer medium (0.25 μM dexamethasone, 0.5 mM IBMX, 1 μg/ml insulin) for 2 days. The cells were then maintained another 2 days in 100 nM insulin and media was replaced thereafter for every 2 days prior to lipid formation. To examine the effects of GME on the differentiation, cells were cultured in MDI differentiation medium in the presence of various concentrations of GME (2.5, 5.0 and 10.0 μg/ml). Results: In 3T3-L1 cells, GME significantly enhanced adipogenic differentiation in a dose-dependent manner (p<0.05). GME also promoted glucose transport evidenced by uptake of Deoxy-D-glucose, 2- [1,2-3H (N)]-in GME-treated cells (p<0.05). However, uptake of glucose was inhibited by 62.9% at highest concentration (10 μg/ml), suggesting inhibition of IRS-1 phosphorylation. Conclusion: Our results suggested that mangosteen extract could be a potential therapeutic agent for managing diabetes via promotion of adipogenesis with mild improvement in glucose utilization in vitro. However, extensive study should be carried out to unravel the underlying molecular event lead to amelioration of diabetes complications.